Physical preparedness of schoolchildren aged 15-16 years old who are engaged in sports tourism - Olena Demyanchuk (Kazimierz Wielki University, 2017)
The article provides information about the physical preparedness of adolescents who are engaged in sports tourism. The purpose of the study is to determine the levels of development of physical qualities of adolescents aged 15-16 who are engaged in sports tourism. The indicators of speed, agility, flexibility, strength, endurance, speed-strength qualities and static balance in tests with open and closed eyes were determined by means of pedagogical testing. The results obtained were processed by the methods of mathematical statistics, which made it possible to determine the levels of development of the studied physical qualities and their dynamics in the age aspect.